Nintendo DS R4 homebrew haven or pirate tool?. - Gladstone, Darren (PC World Philippines)
Revolution for DS (R4)-an unofficial cartridge used for hacking the Nintendo DS handheld game machine-- has been used for crafting DS software and shared freely.